Management of outbreaks of nosocomial pathogens in Neonatal Intensive Care Unit - B. Ghirardi; C. Pietrasanta; F. Ciuffini; M.F. Manca; S. Uccella; A. Lavizzari; L. Pugni; F. Mosca (PAGEPress Publications, 2013)
Outbreaks of nosocomial pathogens are one of the most relevant problems in Neonatal Intensive Care Unit (NICU). Many factors contribute to the onset of an epidemic, including virulence of the pathogen and vulnerability of the infants hospitalized in NICU. Outbreaks are often caused by multidrug-resistant organisms (MDROs). MDROs are defined as microorganisms, predominantly bacteria, that are resistant to one or more classes of antimicrobial agents. MDROs, including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE) and certain gram-negative bacilli (GNB), have important infection control implications. Once MDROs are introduced into a healthcare setting, transmission and persistence of the resistant strain is determined by the availability of vulnerable patients, selective pressure exerted by antimicrobial use, increased potential for transmission from larger numbers of infected or colonized patients ("colonization pressure"), and the impact of adherence to prevention efforts. Often, routine infection control measures are not enough to contain outbreaks, and additional control measures are needed, including implementation of hand hygiene, cohorting of infected/colonized infants, neonatal surveillance cultures, screening of healthcare workers and decolonization of neonates and/or healthcare workers in selected cases. In this review, we report the practices we developed in our NICU to contain an epidemic. These recommendations reflect the experience of the group, as well as the findings of the current literature.